ASSESSMENT OF THE CORRELATION BETWEEN PULMONARY FUNCTION AND COGNITIVE IMPAIRMENT IN OCCUPATIONAL HIGH-RISK WORK ENVIRONMENTS - SUREKHA R; SAMUEL SUNDAR DOSS; ASHOK VARDHAN N; VARADHARAJU B; SANJAY ANDREW RAJARATNAM (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to investigate the correlation between pulmonary function and cognitive performance, assessed through pulmonary function tests (PFTs) and Montreal Cognitive Assessment (MoCA), among workers in high-risk occupational environments. Methods: A cross-sectional study was conducted from March 2024 to January 2025 in Chennai, Tamil Nadu, involving 180 male participants (aged 30–55 years) from five occupational groups (carpenters, construction workers, drivers, painters, and welders) and a control group (computer programmers). PFTs measured forced vital capacity (FVC), forced expiratory volume in 1 s (FEV₁), FEV₁/FVC ratio, and peak expiratory flow (PEF) pre- and post-shift. Cognitive function was assessed using the MoCA, evaluating visuospatial/executive function by the trail making test, naming, attention, language, abstraction, delayed recall, and orientation. Data were analyzed using one-way ANOVA, post hoc Tukey’s tests, and the Kruskal– Wallis test, with statistical significance set at p<0.05. Results: Significant post-shift declines in pulmonary parameters (FVC, FEV₁, PEF, and maximum voluntary ventilation) were observed across all occupational groups (p<0.001), with carpenters and construction workers showing the most pronounced reductions. MoCA scores revealed significant inter-group differences in visuospatial/executive function, language, attention, delayed recall, and orientation (p<0.01). Painters and drivers outperformed carpenters and construction workers in most cognitive domains. The control group exhibited superior pulmonary and cognitive performance. A significant inverse correlation was found between reduced pulmonary function and cognitive deficits, particularly in language and delayed recall. Conclusion: Occupational exposure in high-risk environments is associated with acute pulmonary function decline and specific cognitive impairments, suggesting shared pathophysiological mechanisms such as inflammation and oxidative stress. Routine integration of cognitive and pulmonary assessments in occupational health surveillance is recommended to detect early functional decline and inform intervention strategies.